2020
DOI: 10.1183/23120541.00219-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation referral and uptake from primary care for people living with COPD: a mixed-methods study

Abstract: Pulmonary rehabilitation (PR) for people with COPD leads to clinically significant improvements in quality of life and exercise capacity [1]. In England and Wales, UK, in 2013-2014, only 15% of eligible patients were referred (51% from primary care), of whom 31% did not attend assessment [2]. We aimed to generate a theory-informed understanding of enablers and barriers to PR referral and uptake from primary care.This mixed-methods study [3] used normalisation process theory (NPT) [4] to understand how PR refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Pathological studies of deceased COVID-19 patients revealed edematous lungs with necrotic lesions. The lung tissues exhibited diffuse alveolar damage with formation of hyaline membranes, thrombosis and microangiopathy in the small vessels and capillaries, wide intra-alveolar hemorrhage, vascular congestion, and infiltration of inflammatory cells including inflammatory monocytes and CD4 + and CD8 + T lymphocytes ( Adachi et al, 2020 ; Barton et al, 2020 ; Early et al, 2020 ; Fox et al, 2020 ; Martines et al, 2020 ; Wang C. et al, 2020 ; Xu Z. et al, 2020 ). Extensive neutrophil infiltration was also observed in lung tissue of some deceased patients ( Barnes et al, 2020 ; Fox et al, 2020 ; Tian S. et al, 2020 ; Xu Z. et al, 2020 ).…”
Section: Three Stages Of Immunopathological Pathway To Covid-19 Mortamentioning
confidence: 99%
“…Pathological studies of deceased COVID-19 patients revealed edematous lungs with necrotic lesions. The lung tissues exhibited diffuse alveolar damage with formation of hyaline membranes, thrombosis and microangiopathy in the small vessels and capillaries, wide intra-alveolar hemorrhage, vascular congestion, and infiltration of inflammatory cells including inflammatory monocytes and CD4 + and CD8 + T lymphocytes ( Adachi et al, 2020 ; Barton et al, 2020 ; Early et al, 2020 ; Fox et al, 2020 ; Martines et al, 2020 ; Wang C. et al, 2020 ; Xu Z. et al, 2020 ). Extensive neutrophil infiltration was also observed in lung tissue of some deceased patients ( Barnes et al, 2020 ; Fox et al, 2020 ; Tian S. et al, 2020 ; Xu Z. et al, 2020 ).…”
Section: Three Stages Of Immunopathological Pathway To Covid-19 Mortamentioning
confidence: 99%
“…The multiple factors leading to these missed opportunities, and how to begin addressing them, can appear opaque to service providers. EARLY et al [79] published eye-opening UK-based research reporting the referral and uptake barriers perceived by referrers, pulmonary rehabilitation providers and, crucially, patients (figure 2) [79]. Their mixed-methods study identified multiple potential service barriers relating to service design, referrer training, patient beliefs and data monitoring [79].…”
Section: Physical Activity Exercise and Pulmonary Rehabilitationmentioning
confidence: 99%
“…14 Several studies have been conducted to understand barriers that affect access to PR. [15][16][17][18][19][20][21][22][23][24][25][26] Referral to PR can be influenced by complicated referral processes, lack of knowledge or information about PR, and unclear roles and responsibilities among healthcare professionals (HCPs) concerning referral. Uptake rates can be affected by the patients' beliefs about the benefits of PR, timing, transport and even geographic distance to a program as well as the quality of the HCP's conversation with patients about PR.…”
Section: Introductionmentioning
confidence: 99%